The STATE-OF-THE-ART ON RADIOACTIVE SLUDGE FROM SPENT FUEL REPROCESSING - Agung Prastowo (Indonesian Journal of Physics and Nuclear Applications, 2020)
Radioactive sludge has been produced from the co-precipitation process of spent nuclear fuel reprocessing, which is derivative waste that requires special attention in waste management methods. This study examines the development of research applied by countries with the civilian nuclear program. Proper methods regarding radioactive sludge conditioning are used as a reference for waste management determining radioactive sludge which is one of the main focuses in waste recovery and conditioning (RCD) projects at Orano la Hague, France. Radioactive sludge has been conditioned using bitumen, where the French nuclear safety authority does not permit it because of the radiolysis issue in the waste storage package. Therefore, new methods for bitumen replacement and radioactive sludge storage packages are needed to replace it by the provisions of the French Nuclear Safety Agency. A systematic literature review method is used to provide an analysis of the methods for radioactive sludge waste conditioning that have been synthesized from several related studies to provide an overview of the current issues. The HPing and plasma filtering methods were developed at Sellafield and Hanford with the advantage of reducing the significant volume of waste and chemical composition.